Virtual trial protocol analysis of nursing workload intensity within ICU - Razak N.N.B.A.; Razak A.A.; Pretty C.G.; Ahamad N.H.; Suhaimi F.M.; Jamaluddin U. (Springer Verlag, 2023)
Biomedical engineering; Insulin; Intensive care units; Nursing; Safety engineering; Control performance; Control protocols; Glargine; Intensive-care patients; Model-based OPC; Protocol analysis; Workload intensities; Workload reduction; Patient treatment